2011
DOI: 10.1051/0004-6361/201014726
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the break in the X-ray luminosity function of low-mass X-ray binaries

Abstract: We analyze a flux-limited sample of persistent and bright (with 2-10 keV fluxes exceeding 1.4 × 10 −10 erg s −1 cm −2 ) low-mass X-ray binaries (LMXBs) in our Galaxy. It is demonstrated that the majority of binary systems with X-ray luminosities below log L(erg/s) ∼ 37.3 have unevolved secondary companions (except for those with white dwarf donors), while systems with higher X-ray luminosity harbor predominantly giant donors. Mass transfer in binary systems with giants significantly shortens their lifetime thu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 67 publications
4
31
0
Order By: Relevance
“…This relation was confirmed by observed data by Revnivtsev et al (2011). This relationship is theoretically derived from the timescale of the angular momentum loss via magnetic stellar wind (Taam 1983;Iben & Tutukov 1984).…”
Section: Roche Lobe Overflow Accretion and Luminosity-orbital Period supporting
confidence: 71%
See 1 more Smart Citation
“…This relation was confirmed by observed data by Revnivtsev et al (2011). This relationship is theoretically derived from the timescale of the angular momentum loss via magnetic stellar wind (Taam 1983;Iben & Tutukov 1984).…”
Section: Roche Lobe Overflow Accretion and Luminosity-orbital Period supporting
confidence: 71%
“…1, this dependence of luminosity on the orbital period is represented by the dashed-dotted line. In the same figure, persistent LMXBs containing less-evolved donors (filled triangles) and giant donors (filled squares) are plotted (data are taken from Revnivtsev et al 2011Revnivtsev et al , 2012.…”
Section: Roche Lobe Overflow Accretion and Luminosity-orbital Period mentioning
confidence: 99%
“…Observations of other galaxies have also revealed large populations of accreting objects (Fabbiano 2006), which can be used to reveal information on the star formation history (Grimm et al 2003) and stellar content of these galaxies (Gilfanov 2004). The X-ray luminosity function of the Milky Way can be used to constrain the population and evolution of X-ray-emitting sources in the Galaxy (Grimm et al 2002), which is found to be dominated by accreting binary systems with compact object accretors (BH, NS, and WD; Revnivtsev et al 2011aRevnivtsev et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are only 12 LMXBs in the catalogue of galactic LMXBs (Liu et al, 2007), we have ignored the possible effects of LMXBs in GCs on the LMXB XLFs. The LMXB XLFs are mostly influenced by the collective emission properties of these NS-LMXBs with the break in the XLF either due to the change in the mass transfer rate in the binary systems (Postnov and Kuranov, 2005) or due to fraction of Giant donors in population of LMXBs (Revnivtsev et al, 2011). There are also an appreciable number of transient BH LMXBs, which are either in quiescence and occupy very low luminosity states or undergo outbursts for a brief period of time and occupy high luminosity end of XLFs.…”
Section: Discussionmentioning
confidence: 99%